We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
105
1
avatar

log4(x-6)=1-log4(x-3)

 Feb 21, 2019

Best Answer 

 #1
avatar+18965 
+2

log4(x-6) + log4(x-3) =1

log4((x-6)(x-3) = 1

log4(x^2-9x+18) = 1  

x^2-9x+18 = 4

x^2-9x+14 = 0

(x-7)(x-2) = 0      x = 7 and 2   but since there are no logs of negatives     x = 7

 Feb 21, 2019
edited by Guest  Feb 21, 2019
 #1
avatar+18965 
+2
Best Answer

log4(x-6) + log4(x-3) =1

log4((x-6)(x-3) = 1

log4(x^2-9x+18) = 1  

x^2-9x+18 = 4

x^2-9x+14 = 0

(x-7)(x-2) = 0      x = 7 and 2   but since there are no logs of negatives     x = 7

ElectricPavlov Feb 21, 2019
edited by Guest  Feb 21, 2019

15 Online Users

avatar